PERANCANGAN SISTEM MONITORING SUHU RUANGAN FERMENTASI BAWANG HITAM BERBASIS MIKROKONTROLER - Murtadlo, Muhammad Aliyul; Wibowo, Dimas Wahyu; Rokhman, Syaiful; Amirulloh, Reffan Pandu; Floresko, Septian Caesar; Alhamda, Syahdanny (Edu Komputika Journal, 2019)
Garlic includes a very beneficial plant in processing, both to serve as a spice of cooking or medicine. Garlic can also be processed by fermentation that will produce the Black onion. The fermentation process to produce black onion involves the temperature and humidity in which the consistency must be thoroughly controlled. With the above problem can be done by design of fermentation tool to produce black onion by utilizing information technology. In this tool system control is done by a Wemos D1 R2 microcontroller that has an input in the form of a DHT11 sensor, this sensor will detect the temperature and humidity that are in the fermentation tool. From the results of temperature information and humidity will be displayed in the Mobile application. The Monitoring tool also includes a WiFi module to transmit data on the temperature and humidity conditions of the mobile application.